Local composition control using an active-mixing hotend in fused filament fabrication - Joshua T. Green; Ian A. Rybak; Jonathan J. Slager; Mauricio Lopez; Zachary Chanoi; Calvin M. Stewart; Roger V. Gonzalez (Additive Manufacturing Letters, 2023)
Additive manufacturing with local composition control is uniquely suited for the development and exploration of advanced materials with compositionally graded structures. A fused filament fabrication printer was designed with in situ composition control facilitated by using an active-mixing hotend. Stepper motors drive three filament extruders and a mixing rod in proportions instructed by a print file to control composition and material distribution within extrusions. Composition tailoring was demonstrated by printing specimens with twelve distinct regions each consisting of unique filament mixtures. Local control of composition was demonstrated by printing a variety of specimens with composition gradients having horizontal, vertical, radial, and circumferential orientations. The tensile properties of printed materials were modified by printing with mix ratios of polylactic acid and thermoplastic polyurethane. Eight blend ratios were tested in tension and have tensile moduli ranging from 17.3 to 3480 MPa. These methods demonstrate advanced capabilities that are well suited for manufacturing functionally graded structures.